Effect of Si Content and Morphology on Corrosion Resistance of Anodized Cast Al-Si Alloys. Issue 7 (8th June 2017) - Zhu, Baiwei; Fedel, Michele; Andersson, Nils-Eric; Leisner, Peter; Deflorian, Flavio; Zanella, Caterina
Abstract : This paper investigates the influence of Si content and Si particle morphology on the corrosion protection of anodized oxide layers on Al-Si alloys. Two Al alloys with low Si concentrations (2.43 wt-% and 5.45 wt-%, respectively) were studied and compared with 6082-T6 via electrochemical impedance spectroscopy (EIS) in 3 wt-% NaCl solution prior to oxide layer sealing. Si particles were also modified by the addition of Sr to study the influence of Si particle morphology on the corrosion protection of the oxide layer. The EIS showed that the corrosion protection provided by the oxide layer on Al-Si alloys is significantly affected by the presence of Si particles. Si particles make the oxide layer locally thinner and more defective in the eutectic region, thereby increasing the ease of substrate corrosion attack. However, the addition of Sr can improve the corrosion protection of anodized Al-Si alloys significantly. Furthermore, it was proved that higher Si level influences negatively the anodized oxide corrosion protection due to the higher amount of cracks and defects, but Sr modification is efficient in preventing this negative effect.